2001
DOI: 10.1128/jb.183.18.5223-5229.2001
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of Glucose Transporter Gene Transcription in Kluyveromyces lactis by Glucose Uptake

Abstract: In the respirofermentative yeast Kluyveromyces lactis, only a single genetic locus encodes glucose transporters that can support fermentative growth. This locus is polymorphic in wild-type isolates carrying either KHT1 and KHT2, two tandemly arranged HXT-like genes, or RAG1, a low-affinity transporter gene that arose by recombination between KHT1 and KHT2. Here we show that KHT1 is a glucose-induced gene encoding a low-affinity transporter very similar to Rag1p. Kht2p has a lower K m (3.7 mM) and a more comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The mechanism of glucose signaling in glucose-repressible strains of the Crabtree-negative yeast Kluyveromyces lactis, used increasingly as a model organism in comparative functional genomics (10 -12), is largely unknown; however, the unique hexokinase KlHxk1 encoded by the RAG5 gene, the expression of glucose transporters, and the capacity for glucose transport seem to be involved (13)(14)(15).…”
mentioning
confidence: 99%
“…The mechanism of glucose signaling in glucose-repressible strains of the Crabtree-negative yeast Kluyveromyces lactis, used increasingly as a model organism in comparative functional genomics (10 -12), is largely unknown; however, the unique hexokinase KlHxk1 encoded by the RAG5 gene, the expression of glucose transporters, and the capacity for glucose transport seem to be involved (13)(14)(15).…”
mentioning
confidence: 99%
“…5. Several studies have shown a correlation between respiration/fermentation and sugar transport (16,24,27,38), suggesting control of assimilation by fermentation due to a limitation of sugar uptake. It is notable that HGT1 is highly inducible, as the introduction of additional sugar transporter genes was shown to allow K. lactis to grow in the absence of respiration (16), and it is even more notable that the HGT1 gene is inactivated, suggesting that the mutation in HGT1 of strain B1 may compensate for the effects of the increased HGT1 gene expression and limit sugar uptake, thus preventing a too massive carbon uptake, which would be deleterious for the cell.…”
mentioning
confidence: 99%
“…The former is only induced by high glucose, whereas induction of HXT3 expression by glucose is independent of sugar concentration. Regulation of LGT1 resembles more that of lowaffinity glucose transporters of K. lactis, KHT1 and RAG1, which show an enhanced expression with the external glucose concentration (Chen et al, 1992;Milkowski et al, 2001). We also analysed whether the Rgt1p and Mig1p consensus binding sites found in the promoter region of LGT1 were functional.…”
Section: Induction Of Lgt1 Expression Is Dependent On Glucose Concentmentioning
confidence: 99%
“…In spite of the phylogenetic proximity of this yeast to S. cerevisiae, the differences observed between the two species, demonstrate that the behaviour of T. delbrueckii cannot be directly inferred from that of S. cerevisiae. Furthermore, and specifically in what regards sugar transport, results from previous work have shown that other yeast species, also phylogenetically close to S. cerevisiae, show relevant differences at this level (Gonçalves et al, 2000;Milkowski et al, 2001). Therefore, an indepth investigation is required to gain insight into the function and regulation of T. delbrueckii sugar transporters.…”
Section: Introductionmentioning
confidence: 99%